Enhancing Vocabulary Learning Through the Blooket Application: Effects on Motivation and Achievement Among Arabic Learners - Salsabila, Octa Syakila; Abidin, Munirul; Yurisa, Penny Respati (Abjadia : International Journal of Education, 2025)
The implementation of the Blooket game Fishing Frenzy mode has been proven effective in Arabic vocabulary learning at the elementary level. The use of Blooket in learning creates an enjoyable atmosphere, making students actively engaged and preventing boredom. This study aims to analyze the application of Blooket in Arabic vocabulary learning at MIN 1 Kota Malang.The research method used is a quasi-experimental design with a pretest-posttest control group design. The study sample consists of 56 students divided into an experimental group using Blooket and a control group using conventional methods. The research instrument includes an Arabic vocabulary test, and the collected data was analyzed using SPSS 20. The results show a significant improvement in students' learning outcomes after implementing the Blooket game, as reflected in the comparison between pre-test and post-test scores, with an average N-Gain of 77.8. Additionally, hypothesis testing results indicate a significance value of 0.006, which is lower than 0.05, leading to the rejection of Ho and acceptance of Ha. Based on these findings, it can be concluded that the implementation of the Blooket game effectively enhances students' interest and learning outcomes in Arabic vocabulary.